Antiretroviral Concentrations in Hair Strongly Predict Virologic Response in a Large Human Immunodeficiency Virus Treatment-naive Clinical Trial. (3rd September 2018) - Gandhi, Monica; Bacchetti, Peter; Ofokotun, Igho; Jin, Chengshi; Ribaudo, Heather J; Haas, David W; Sheth, Anandi N; Horng, Howard; Phung, Nhi; Kuncze, Karen; Okochi, Hideaki; Landovitz, Raphael J; et al.
Abstract: Concentrations of antiretrovirals in hair are associated with virologic outcomes in cohorts of human immunodeficiency virus (HIV)-positive individuals but have never been examined in a clinical trial. We show for the first time the predictive utility of hair antiretroviral concentrations in a large HIV treatment-naive trial (AIDS Clinical Trials Group protocol A5257).